Protection by Neuroglobin Expression in Brain Pathologies - Baez, Eliana; Echeverria, Valentina; Cabezas, Ricardo; Ávila-Rodriguez, Marco; Garcia-Segura, Luis Miguel; Barreto, George E. (Frontiers in Neurology, 2016)
Astrocytes play an important role in physiological, metabolic and structural functions and, when impaired, they can be involved in various pathologies including Alzheimer, focal ischemic stroke and traumatic brain injury. These disorders involve an imbalance in the blood flow and nutrients such as glucose and lactacte, leading to biochemical and molecular changes that cause neuronal damage, which is followed by loss of cognitive and motor functions. Previous studies have shown that astrocytes are more resilient than neurons during brain insults as a consequence of their more effective antioxidant systems, transporters and enzymes, which made them less susceptible to excitotoxicity. In addition, astrocytes synthesize and release different protective molecules for neurons, including neuroglobin, a member of the globin family of proteins. After brain injury neuroglobin expression is induced in astrocytes. Since neuroglobin promotes neuronal survival, its increased expression in astrocytes after brain injury may represent an endogenous neuroprotective mechanism. Here, we review the role of neuroglobin in the CNS, its relationship with different pathologies, and the role of different factors that regulate its expression in astrocytes.